The Role of Indian English Drama in Learning Second Language Teaching (English) (European journal of volunteering and community-based projects, 2021)
The aim and objective of this study are to research the role of drama performance in university, especially in teaching within the literature and non-literature student of B. A course of Maulana Azad National Urdu University, Hyderabad. It’s a case study of the utilization of drama during a language class, describing the course structure and classroom procedures. The study was administered within the second semester of the 2019 academic years during the rehearsals of Habib Tanvir’s Agra Bazar and Samuel Becket expecting Godot. It comprises the private perspectives of a gaggle of researchers from various departments and different ages, also as language teachers, who have successfully accomplished and achieved their goals, also as analyzed the outcomes, posing challenges and potential strategies for teaching language to international learners. Finally, it supports drama as a medium for constructive and conceptual learning.